2018
DOI: 10.1177/2167479518816104
|View full text |Cite
|
Sign up to set email alerts
|

“We Are a Football Family”: Making Sense of Parents’ Decisions to Allow Their Children to Play Tackle Football

Abstract: Parents of middle school–aged children face a true dilemma as they consider whether to allow their children to play tackle football. The sport is cited as one that fosters a number of intangible benefits but is increasingly mentioned as dangerous for youth participants. This study employed a sensemaking theory framework to explore the family, community, and media dynamics that influence how parents made sense of their football decisions. We interviewed 12 married couples about their decisions allowing their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 45 publications
(58 reference statements)
1
23
0
1
Order By: Relevance
“…Indeed, Bremer (2012) suggested that, for many families in Western culture, participation in youth sports is "a way of life" (p. 245). For some families, sport also is a central component of their identity (Boneau, Richardson, & McGlynn, 2020), as many families make financial and social sacrifices so their children can participate in sports (Dorsch, Smith, & McDonough, 2009). With the respite from youth sports, a primary activity for families has been suspended, necessitating adjustments to the family routine.…”
Section: Psychological Impactsmentioning
confidence: 99%
“…Indeed, Bremer (2012) suggested that, for many families in Western culture, participation in youth sports is "a way of life" (p. 245). For some families, sport also is a central component of their identity (Boneau, Richardson, & McGlynn, 2020), as many families make financial and social sacrifices so their children can participate in sports (Dorsch, Smith, & McDonough, 2009). With the respite from youth sports, a primary activity for families has been suspended, necessitating adjustments to the family routine.…”
Section: Psychological Impactsmentioning
confidence: 99%
“…Personal and community dynamics also influence sport attitudes and participation (Tamminen et al, 2017). Prior work has discussed the influence of family characteristics on decisions to allow children to play tackle football (Boneau et al, 2020). Parents' history, community factors, and relationships with teammates and coaches affect sport participation (Cranmer, 2018).…”
Section: Youth Sport Socializationmentioning
confidence: 99%
“…Walaupun sepakbola banyak digemari, namun beberapa orang tua menghadapi dilema dan kecemasan terkait aktivitas yang ada dalam olahraga sepakbola termasuk di SSB sekalipun. Salah satu dilema yang dihadapi oleh orang tua saat anaknya masuk ke dalam kegiatan SSB adalah adanya gerakan yang membayakan seperti tackle (Boneau et al, 2020). Memasukkan anak muda ke dalam SSB juga memiliki risiko lain seperti gegar otak, namun medis yang professional harus memberikan informasi kepada orang tua terkait penanganan dan cara pemulihannya (Rieger et al, 2018).…”
Section: Pendahuluanunclassified